Peningkatan Keaktifan dan Hasil Belajar Matematika dengan Strategi Mind Mapping pada Siswa Kelas VII Semester Genap MTs Negeri Walen tahun 2014/2015 - Widyarsiwi, Nurani, Drs. Slamet HW, M.Pd (2015)
This study aims to determine the increase in activity and class VII student learning outcomes through Mind Mapping strategy on the subject of Build rectangular space, this type of research is a classroom action research (PTK) . The subjects were students of class VII MTs D Walen Simo academic year 2014/2015 the number of students 28. The method of blunting the data used is the method of observation, field notes, documentation and test. Techniques of data analysis in this study transactions are carried out with a qualitative descriptive. Qualitative descriptive analysis carried out by the method of the groove. Data were analyzed since the act of learning every action during the two rounds. Results of this research are: 1) there is an increase in activity of students in the subject of mathematics learning rectangular flat wake. It can be seen from the number of students who: a) asking the question 67,9%, b) 70,0% answered the question, c) conveying the idea 57,1%, d) presented the results of 67,9% no increase student learning outcomes, this can be seen from the number of students who: a) considering 75,0% , 67,8% understand, analyze 60,7%. The conclusion of this study is mind mapping strategies can enhance the activity and student learning outcomes in mathematics.